(3QSGdI aj SYGOI GdEfSGfs
(3ChdgG (B:s
(3hHYO aNaja Ydi ef NUg Gddg HGdgeI GdYdjI hLYd dfaSg ai cd aVjdI bOe s
(3BNQgG (B:s
(3hbO YdeJ ajg Ydi MGd cdGekG GLJgOJ ajg Cf jdhM efg s
(3Vef eLehY , JQJjHgG (B: (3GdKGfis
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3MceI JjehQ (B86) s
Keywords: (3GdadSaI hGdefWbs